Assessment of Protein Quality and Nutritional Characteristics of Commonly Consumed Pulses in the Caribbean Diet by Different In Vitro Assays - Daniel J. Thomas; Zhanhui Lu; Yolanda Brummer; Yan Zhu; Ronghua Liu; Lili Mats; Rong Tsao; D. Dan Ramdath; Matthew G. Nosworthy (Foods)
Pulses, the dried seeds of leguminous plants, form an important part of the diets of many cultures, including Caribbean cuisine, and are a rich source of protein, carbohydrates, and antioxidants while being low in fats. This study examined the effect of a traditional home-cooking method on the nutritional characteristics of pulses commonly consumed in the Caribbean: red kidney beans and cranberry beans (Phaseolus vulgaris L.), cowpeas (Vigna unguiculata L.), and pigeon peas (Cajanus cajan L.). Protein quality, determined via three in vitro protein digestibility methods, starch, and phenolic content were determined in pre- and post-cooked samples using established methods. Pulses contained 20–26% protein, and cooking improved protein digestibility on average by 14.0 ± 2.5% (p < 0.05). However, notable differences in digestibility were observed: it was higher in static assays (pH-Drop and pH-Stat) than in the two-step digestibility assay. Average protein digestibility-corrected amino acid score (IVPDCAAS) among cooked pulses was 0.81 ± 0.14, with the highest in cranberry bean (0.82) and cowpea (0.88). Cooking modified pulse starch profiles by increasing total digestible starch. However, resistant starch and slowly digestible starch fractions accounted for approximately 20–25% of total cooked starch content. While total phenolic content (TPC) and antioxidant activity were reduced with cooking, they were within expected ranges for cooked pulse flours; however, they were higher in bean (P. vulgaris) varieties than cowpea and pigeon pea. These findings support the promotion of increased pulse consumption in Caribbean diets. Home cooking is a simple method to enhance pulse protein quality through enhancing digestibility; however, in vitro protein digestibility assays may require further standardization.